1979
DOI: 10.1177/030098587901600301
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Malformations and Hemangiomas of the Canine Spinal Cord

Abstract: An arteriovenous malformation and two hemangiomas in the canine spinal cord were found in three dogs. The malformation was ventral, extramedullary and largely subdural. Chronic hypoxia, consequent upon the shunt, had led to extensive local edema, necrosis and hemorrhage at T13-L1. Prominent intramedullary perivascular fibrosis, mineralization and obliteration were the presumed consequences of the hemodynamic insult. The hemangiomas, one of which was multiple, were deep lesions that produced compressive changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
50
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 5 publications
0
50
0
Order By: Relevance
“…This sequence would unlikely have been useful to differentiate hemangioblastoma from other neoplasms having an hemorrhagic component as previously described in some meningiomas, 16 gliomas, 14 hemangiomas, 17 or metastatic neoplasms. 18 A 2003 publication 2 suggested that some earlier canine reports 19 could have misdiagnosed some hemangioblastoma cases as hemangiomas because of confusing histopathological findings. The MRI characteristics of intracranial and intramedullary hemangiomas have been published recently, 17, 20 but the contrast enhancement of the reported intracranial hemangiomas were patchy and heterogeneous, while histologically they represent distinct entities compared to the case reported here and the previously reported intramedullary case.…”
Section: Discussionmentioning
confidence: 99%
“…This sequence would unlikely have been useful to differentiate hemangioblastoma from other neoplasms having an hemorrhagic component as previously described in some meningiomas, 16 gliomas, 14 hemangiomas, 17 or metastatic neoplasms. 18 A 2003 publication 2 suggested that some earlier canine reports 19 could have misdiagnosed some hemangioblastoma cases as hemangiomas because of confusing histopathological findings. The MRI characteristics of intracranial and intramedullary hemangiomas have been published recently, 17, 20 but the contrast enhancement of the reported intracranial hemangiomas were patchy and heterogeneous, while histologically they represent distinct entities compared to the case reported here and the previously reported intramedullary case.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular malformations in animals resulting in myelopathy are reported infrequently 1 . In dogs, five reports have been published: intramedullary hamartoma, 1 arteriovenous malformation in the cervical 2 and thoracolumbar region, 3 a venous aneurysm 4 and a lumbosacral angioectatic malformation 5…”
Section: Discussionmentioning
confidence: 99%
“…In human brain, vascular hamartomas are classified as capillary telangiectasias, cavernous angiomas, and arteriovenous or venous malformations [8]. In veterinary literature, vascular hamartomas have been rarely described in canine [11], feline [12], equine [5] and bovine brain [1], whereas single cases of such malformations have been reported in the spinal cord of a dog [4], a Hereford calf [3], a goat [9] and a foal [6]. Classification of such lesions remains confusing, and terminology among the reports tends to vary.…”
mentioning
confidence: 99%